EFFECTIVENESS OF CHILDREN'S COMPETITIVENESS IN THE USE OF POPULATION ADMINISTRATION - Dedi Epriadi; Razaki Persada; Ukas Ukas (DIA: Jurnal Administrasi Publik, 2019)
One of the demands on the Department of Population and Civil Registration of Bungo Regency is to provide services to the community to achieve orderly population administration but from the writer's initial observation, data collection officers in the field found it difficult to optimize data collection, because SAD lives in nomadic life. detected by the assessor. While the purpose of this study was to determine the effectiveness of the SAD data collection at the Population and Civil Registry Office of Bungo Regency. In this case, it will be analyzed how the effectiveness of SAD data collection relating directly to the orderly Administration which is set forth in the regulation of the Minister of the Interior Number: 11 of 2010 concerning guidelines on data collection and issuance of population documents for vulnerable population administration. In this study, researchers used a descriptive qualitative research method by looking at research subjects who became this study. While in data collection techniques, researchers use the literature study technique, field studies consisting of observations, interviews, and documentation. Descriptive data analysis techniques in analyzing data, i.e. with data that has been collected from interviews and documentation or library studies will be analyzed and interpreted to find out its meaning and meaning. The results of the study prove that effective data collection will spur an increase in the orderly administration of optimal population, besides, it is recommended to the Department of Population and Civil Registration to register in a sustainable manner in the Bungo Regency, especially to remote communities, although there are still many deficiencies in it but have appeared changes and differences in Bungo District.